Utilization rates and clinical outcomes of hepatitis C positive donor hearts in the contemporary era - Madan, Shivank; Patel, Snehal R; Rahgozar, Kusha; Saeed, Omar; Murthy, Sandhya; Vukelic, Sasa; Sims, Daniel B; Shin, Jooyoung Julia; Goldstein, Daniel J; Jorde, Ulrich P (The Journal of heart and lung transplantation, 2019)
Hepatitis C virus (HCV) donors should be categorized as HCV-viremic (antibody [Ab] negative or positive/Nucleic Acid testing [NAT] positive) or HCV Ab nonviremic (Ab /NAT ). Whereas recipients of hearts from HCV-viremic donors will develop viremia but can be cured of HCV shortly after transplant with direct-acting antivirals (DAAs), recipients of hearts from HCV Ab nonviremic donors are highly unlikely to become viremic or require DAAs. Given this important difference in risk, we assessed the utilization trends and post-heart-transplantation outcomes of HCV-naive (Ab /NAT ), HCV-viremic, and HCV Ab nonviremic donor hearts. A total of 26,572 adult donors (≥18 years) with information on HCV Ab and NAT status were identified in the United Network for Organ Sharing registry between August 2015 and June 2018 for utilization rates. Adult heart transplant recipients of these donors were compared for primary graft failure (PGF) at 90 days and 1-year recipient survival. A total of 96 HCV Ab nonviremic and 135 HCV-viremic adult donor hearts were transplanted during the study period. The utilization rates of both HCV Ab nonviremic (1.4%-23.4%) and HCV-viremic (0.7%-25.4%) donor hearts increased significantly approaching HCV-naive rates (29.04%). There was no significant difference in rates of PGF and 1-year survival between recipients in the 3 donor HCV groups. We also used (1:3) propensity score matching and found similar 1-year survival in different donor HCV groups (HCV-naive vs HCV Ab nonviremic, p = 0.59, and HCV-naive vs HCV-viremic, p = 0.98). Recipients of HCV-viremic and HCV Ab nonviremic donor hearts had equivalent risk of PGF and 1-year mortality compared with recipients of HCV-naive donor hearts. Although only HCV-viremic organs require DAAs and the risk of coronary artery vasculopathy after treated HCV infection has not been defined, the utilization rates of both HCV Ab nonviremic and HCV-viremic adult donor hearts have increased at an equal pace now approaching HCV-naive rates.